Characterization of Antibiotic Resistant Salmonella spp Isolated from Chicken Eggs of Dhaka City - Ahmed, M. M.; Rahman, M. M.; Mahbub, K. R.; Wahiduzzaman, M. (Journal of Scientific Research, 2010)
In present study, the occurrence of Salmonella in local chicken eggs and their pattern of antibiotic resistance were determined. 100 egg samples collected from different locations of Dhaka city were analysed and Salmonella spp were found in 8% of the samples. Among all presumptive Salmonella isolates, 8 isolates were confirmed as Salmonella enterica subsp. salamae (4%), Salmonella enterica subsp. indica (1%), Salmonella Paratyphi-A (1%), Salmonella bongori (1%) and Salmonella Choleraesuis (1%) on the basis of serotyping and biochemical analysis. These isolates were subjected to susceptibility test against 10 antibiotic disks. All the isolates were found chloramphenicol sensitive. The highest percentage of resistance (87.5%) was found to amoxicillin and ampicillin. Resistance against erythromycin, cephalexin, doxycycline hydrochloride, ceftazidime, doxycycline and nalidixic acid was also found significant ranging from 25% to 62.5%. Salmonella isolated from egg shell surface were found more antibiotic resistant than that of egg yolk and white. The present study suggests that poultry eggs are potential reservoir of antibiotic resistant Salmonellae. Keywords: Egg; Salmonella; Characterization; Antibiotic resistance. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6109 J. Sci. Res. 3 (1), 191-196 (2011)